Development of a Social-Media–Based Tele-Rehabilitation and Caregiver Education Protocol for Stroke Survivors Stratified by Functional Independence Measure Levels: Pilot Randomized Study Protocol - Trupti Deshmukh; Amal Bhattacharya; Bhavana Gadhavi (The Bioscan, 2025)
Background: Stroke remains a leading cause of long-term disability worldwide. Despite the proven benefits of structured rehabilitation, many stroke survivors—particularly in resource-limited settings—lack access to continuous facility-based therapy due to geographical, economic, and infrastructural barriers. Tele-rehabilitation, delivered through accessible platforms such as Zoom or WhatsApp, has emerged as a promising approach to bridge these gaps. Caregivers play a crucial role in stroke recovery, yet caregiver education is rarely integrated into digital rehabilitation programs. Objective: To describe the design of a pilot randomized controlled trial evaluating the feasibility, acceptability, and preliminary efficacy of a social-media–based tele-rehabilitation plus caregiver education (SM-TR+CE) protocol stratified by Functional Independence Measure (FIM) levels, compared with conventional in-center neurorehabilitation. Methods: This pilot RCT will enroll 20 participants (10 per arm) within one year of ischemic stroke or TIA, stratified by FIM dependency level. Participants will be randomized to either SM-TR+CE or conventional care. The intervention will last 12 weeks, comprising three supervised sessions per week supplemented by caregiver training modules, brochures, and digital reinforcements. Primary outcomes are feasibility metrics (recruitment, retention, adherence, and adverse events). Secondary outcomes include changes in FIM, Fugl-Meyer motor scores, caregiver burden, and caregiver quality of life. Discussion: This pilot trial is designed to assess feasibility and provide variance estimates for future sample size calculations. While not powered for definitive efficacy conclusions, it will inform the refinement of a scalable tele-rehabilitation framework that integrates caregiver education tailored by functional dependency levels. Conclusion: The study protocol represents a step toward developing an accessible, cost-effective, and stratified tele-rehabilitation model for stroke survivors and their caregivers, with potential to guide a future definitive RCT.